Ferrocene Decorated N‐doped Carbon Modified Electrode with Enhanced Electrocatalytic Activity towards Non‐enzymatic Glucose Detection. Issue 5 (2nd December 2021) - Mathi, Selvam; Karthikeyan, Venkatraman; Jayabharathi, Jayaraman
Abstract: The nitrogen doped carbon (NDCN) have been synthesized by flame synthetic method to prepare ferrocene decorated NDCN. The hydrolysis product (FC‐SH) of ferrocene benzyne derivative (FC‐SAc) was immobilized onto NDCN modified GCE and used for glucose detection with high sensitivity. Cyclic voltammetric analysis reveal that FC‐S‐NDCN/GCE exhibit excellent activity for glucose oxidation when compared to FC/GCE. The FC‐S‐NDCN/GCE with wide linear responses range from 0.001 to 0.01 mM with the regression co‐efficient of 0.998. The FC‐S‐NDCN/GCE show low detection limit (LOD) of 0.08 μM and exhibit sensitivity of 1580 μA mM −1  cm −2 . The FC‐S‐NDCN glucose sensor exhibit wide linear range, high sensitivity and lower detection limit on determination of glucose. Abstract :